All-weather anti-salt solar desalination using a sandwich evaporator with thermal storage and asymmetric wettability - Yimin Qu; Changliang Lu; Ziyue Zhang; Xi Wen; Xuanli Jing; Tiaohong Zhang; Ting Lv; Dajian Huang; Yanping Wang; Xiaohu Qiang (Chemical Engineering Journal, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Solar-driven degradation of HEDP and simultaneous phosphorus recovery from electroplating wastewater via a Cu (III)-mediated biochar electro-Fenton system - Shibo Zhao; Yanping Cui; Qiao Huang; Xian Xiang; Yuqing Qu; Chu Xiong; Bolin Li; Caixia Wen (Chemical Engineering Journal, 2026)

Ammonium-activated peracetic acid for enhanced tetracycline degradation: Performance and mechanism - Qiao Huang; Yanping Cui; Bolin Li; Chu Xiong; Xian Xiang; Yuqing Qu; Shibo Zhao; Caixia Wen (Environmental Research, 2025)

Interfacially synergistic Photothermal enhancement for solar evaporation by palygorskite-carbon nanotube/chitosan aerogels - Yimin Qu; Changliang Lu; Gaofeng Zhang; Zhu Hu; Dajian Huang; Xiaohu Qiang; Yanping Wang (Desalination, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

Interpretation of the Budyko framework for monthly evapotranspiration prediction of individual basins - Hao Sun; Xingwang Wang; Yanping Qu; Juan Lyu; Hehe Cai; Xuejun Zhang (Atmospheric Research, 2025)

Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping Qu; Hongcui Li; Ibrahim Yakub; Wen He; Wenchan Dong; Mohamad Hardyman Barawi; Sirui Wang; Huimin Ma; Zhenpeng Zhu (Water, Air, & Soil Pollution, 2025)

Vacancy engineering-induced spin polarization in heterogeneous phosphides by simple iron salt infiltration for efficient overall water splitting - Xuanning Qin; Zebin Yu; Zimu Zhang; Zuoyu Qin; Han Pang; Boge Zhang; Yanping Hou; Jun Huang; Ronghua Jiang; Jiayi Qu (Chemical Engineering Journal, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

Involvement of a rice mutation in storage protein biogenesis in endosperm and its genomic location - Huaidong Tian; Ying Li; Yanping Guo; Yajuan Qu; Xiaoye Zhang; Xiaoxian Zhao; Xinya Chang; Baohua Tian; Guangyuan Wang; Xiangmei Yuan (Planta, 2024)

Estimating and partitioning evapotranspiration in a film mulched cropland with shallow groundwater by the improved dual source model - Xingwang Wang; Qiangli Wei; Weishu Wang; Shuai Wang; Zailin Huo; Yanping Qu; Juan Lyu; Huimin Lei (Journal of Hydrology, 2024)

Determining the response of ecological drought to meteorological and groundwater droughts in Northwest China using a spatio-temporal matching method - Tianliang Jiang; Xiaoling Su; Yanping Qu; Vijay P. Singh; Te Zhang; Jiangdong Chu; Xuexue Hu (Journal of Hydrology, 2024)

SlCNR regulates postharvest water loss and wax accumulation in tomato fruit and directly represses the transcription of very-long-chain (VLC) alkane biosynthesis-related genes SlCER1-2 and SlCER6 - Di Chen; Tingyu Wang; Hua Huang; Qiaoli Zhang; Xue Chen; Zongyan Sun; Yanping Song; Yuetong Yi; Chengxia Liu; Donald Grierson; Jiankang Cao; Daqi Fu; et al. (Postharvest Biology and Technology, 2024)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

A spatiotemporal deconstruction-based approach for identifying flash drought expansion: Normalized Area-Time Accumulation curve - Ruiqi Chen; Yi Liu; Ye Zhu; Liliang Ren; Yanping Qu; Jason A. Otkin; Vijay P. Singh (Journal of Hydrology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

The development and future frontiers of global ecological restoration projects in the twenty-first century: a systematic review based on scientometrics - Xue Jiang; Yitao Sun; Yanping Qu; Houyuan Zeng; Jingtian Yang; Kaiyou Zhang; Lei Liu (Environmental Science and Pollution Research, 2023)

Climate and management impacts on the spatiotemporal dynamics of water-carbon fluxes in the North China Plain - Xingwang Wang; Huimin Lei; Jiadi Li; Yanping Qu; Dongdong Kong; Zailin Huo (Agriculture, Ecosystems & Environment, 2023)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Cefquinome-Loaded Microsphere Formulations in Protection against Pneumonia with Klebsiella pneumonia Infection and Inflammatory Response in Rats - Shaoqi Qu; Cunchun Dai; Fenfang Yang; Tingting Huang; Zhihui Hao; Qihe Tang; Haixia Wang; Yanping Zhang (Pharmaceutical Research, 2019)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Alteration of integrin-associated protein (CD47) on experimental porcine eperythrozoonosis - Wei Li; Ning Du; Binrui Xu; Weixing Dong; Zhe Qu; Yong Wang; Yanping Sui (Veterinary Research Communications, 2008)